Digital Literacy Among Elementary School Teachers: Age and Year of Service Perspective Review - Fazis, Muhammad; Safrizal; Yulia, Resti (Universitas Pendidikan Ganesha, 2024)
The government's policy on increasing teachers in the aspect of mastery of technology is a requirement that must be met, this is intended so that the learning process can be carried out more effectively and efficiently by utilizing technology. This study aims to analyze and measure the digital literacy skills of elementary school teachers. This type of research uses a quantitative descriptive method. The subjects of this study were 73 elementary school teachers, who were taken using the quota sampling technique. The data collection technique that the researchers used was a questionnaire to determine the digital literacy abilities of elementary school teachers. The data that has been collected was analyzed using descriptive statistical analysis. The results showed that the literacy skills of elementary school teachers throughout Tanah Datar regency both in the aspects of media literacy, information literacy, and technology literacy for each review (age and years of service) were in the low category, with an average achievement of 2.41 for the view of teacher age and 2.43 for the view of years of service. So it can be concluded that the digital literacy skills of elementary school teachers in Tanah Datar regency are in the low category, both in terms of age and years of service.